ASUHAN KEBIDANAN KEBERLANJUTAN DI PRAKTIK MANDIRI BIDAN : LAPORAN KASUS: CONTINUITY OF MIDWIFERY CARE (COC) IN MIDWIFE’S INDEPENDENT PRACTICE: A CASE REPORT - Sari, Dwi Siska Mayang; Hanum , Sri Mukhodim Farida (WELL BEING, 2025)
By offering holistic and ongoing treatments from pregnancy, childbirth, the postpartum period, and family planning, Continuity of Care (COC) significantly lowers mother and infant mortality. This case study uses a qualitative method with a thorough case study approach to discuss how COC was implemented for Mrs. H at the Sri Herlies Independent Midwife Practice in Surabaya. Third-trimester prenatal appointments, labor assistance, newborn care, postpartum monitoring, and contraception advice are among the services offered. Mrs. H’s pregnancy progressed well, supported by an Hb level of 11.5 g/dL. She delivered spontaneously without an episiotomy, welcomed a healthy baby, and initiated early breastfeeding. Mild postpartum discomfort was managed with education and deep-breathing techniques. She chose the three-month injectable contraceptive, safe for breastfeeding mothers. Keywords: Continuity of Care, Midwifery Care, Pregnancy, Childbirth, Contraceptive